Interventions in agriculture for nutrition outcomes: A systematic review focused on South Asia. (January 2019) - Bird, Frances A.; Pradhan, Aliza; Bhavani, R.V.; Dangour, Alan D.
Highlights: Nutrition-sensitive agricultural interventions often support vulnerable populations. Evidence shows interventions improve intermediate outcomes like dietary diversity. Limited evidence that interventions improve long-term outcomes like child growth. Unintended consequences for women's workload and sustainability need attention. LANSA has significantly extended range and scope of interventions in South Asia. Abstract: Research on the potential impact of interventions in agriculture on nutrition outcomes is of particular relevance in South Asia where agriculture-related activities are a major source of livelihoods for large sections of society and where the population suffers from one of the highest global burdens of malnutrition in all its forms. This systematic review aims to assess the strength of the available evidence that agricultural interventions have an impact on intermediate and final nutrition outcomes in India, Bangladesh, Nepal, Pakistan and Afghanistan. We searched five literature databases and reference lists of previous systematic reviews to identify peer-reviewed studies published between 2012 and 2017, detailing impacts of household- or farm-level agricultural interventions on nutritional outcomes in South Asia. We identified six intervention studies (reported in nine papers) conducted in Bangladesh (two studies), India (two studies) and Nepal (two studies). The majority of studies examined the impact of provision of seed, plants and training to increase home garden fruit and vegetable production with or without integrated poultry provision and training. Other studies evaluated the impact of livestock or aquaculture provision and training. Study designs and quality were mixed; heterogeneity across studies precluded formal meta-analysis. Interventions had a positive impact on intermediate outcomes on the pathway from agricultural intervention to nutritional or health status including dietary quality and dietary diversity of households and individuals (reported in seven papers). The evidence on the impact on final nutritional outcomes was mixed: one paper reported that home gardens with poultry reduced the odds of anaemia but there was no convincing evidence of an impact of agricultural interventions on child anthropometric measurement (reported in four papers). In recent years, the Leveraging Agriculture for Nutrition in South Asia (LANSA) research programme consortium has significantly expanded research on agricultural interventions for nutrition outcomes by conducting and commissioning a suite of formative and feasibility studies that have extended both the range and geographic location of interventions under study. This expanding body of research should, in the future, enable the identification of cost-effective interventions to enhance the impact of agricultural interventions sustainably to improve nutrition outcomes especially in women and children in South Asia.